Discover the Driving Forces behind Purchase Intention in Indonesia’s Beauty Industry - Theresia Omiwa Oktariani; Affiana Aulia (Universitas Airlangga, 2024)
Background: The beauty sector is expanding significantly in Indonesia. As Indonesia's domestic beauty sector grows, consumers must select goods that meet their demands and are licensed by Indonesian Food and Drug Authority (BPOM). It is crucial for beauty sector companies in Indonesia to identify the drivers that influence consumer intention to purchase beauty products. Objective: This study aims to examine the impact of social media marketing activity, emotional branding, price perception, and online customer review variables on purchase intention. Method: A quantitative research design was utilized in this study with 100 respondents who provided information online regarding their intention to purchase products in the Indonesian beauty industry. Results: Price perception and social media marketing activity has been shown in this study to impact purchase intention in the Indonesian beauty industry. Emotional branding and online customer reviews, on the other hand, don't affect people's intention to buy in the Indonesian beauty business. Conclusion: This research highlights the factors that influence purchase intention in the Indonesian beauty industry. The findings of this study indicate that social media marketing activity and price perception are significant drivers of consumer intention to purchase beauty products. Keywords: Emotional Branding; Online Customer Review; Price Perception; Purchase Intention; Social Media Marketing Activity